Promise of Chemokine Network-Targeted Nanoparticles in Combination Nucleic Acid Therapies of Metastatic Cancer - Xie, Ying (Wiley Interdiscip Rev Nanomed Nanobiotechnol, 2018)
Chemokines and chemokine receptors play key roles in cancer progression and metastasis. Although multiple chemokines and chemokine receptors have been investigated, inhibition of CXCR4 emerged as one of the most promising approaches in combination cancer therapy, especially when focused on the metastatic disease. Small RNA molecules, such as siRNA and miRNA, represent new class of therapeutics for cancer treatment through RNA interference-mediated gene silencing. However, the clinical applicability of siRNA and miRNA is severely limited by the lack of effective delivery systems. There is a significant therapeutic potential for CXCR4-targeted nanomedicines in combination with the delivery of siRNA and miRNA in cancer. Recently developed CXCR4-targeted polymeric drugs and nanomedicines, including cyclam- and chloroquine-based polymeric CXCR4 antagonists are introduced here and their ability to deliver functional siRNA and miRNA is discussed.